CORPORATE SOCIAL RESPONSIBILITY (CSR) AND ESG INTEGRATION: INVESTOR PERCEPTIONS AND OUTCOMES - Purwati Purwati; Keti Purnamasari; Chintia Romadayanti (Yayasan Adra Karima Hubbi, 2026)
The increasing emphasis on sustainability in global financial markets has intensified the integration of Corporate Social Responsibility (CSR) and Environmental, Social, and Governance (ESG) principles into investment decision-making. Investors are no longer focused solely on financial returns but increasingly consider non-financial performance as an indicator of long-term value, risk management, and corporate resilience. This study aims to examine investor perceptions of CSR and ESG integration and to analyze how these perceptions influence investment outcomes and corporate performance. The research adopts a qualitative-analytical design based on a systematic review of peer-reviewed journal articles, institutional reports, and secondary financial data related to ESG investing and responsible investment practices. The findings indicate that strong CSR engagement and effective ESG integration positively shape investor confidence, enhance corporate reputation, and are associated with improved financial performance and lower perceived risk. The study concludes that CSR and ESG integration function not merely as ethical considerations but as strategic financial factors that influence investor behavior and market outcomes. Effective alignment between corporate responsibility initiatives and ESG frameworks is therefore essential for firms seeking sustainable competitive advantage and long-term investor support in an increasingly sustainability-oriented investment landscape.